Analysis of electrical energy consumers operation in the heating plant with proposal of energy savings measures - Nikolic, Aleksandar B; Antic, Radoslav (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
The results of power quality measurements, obtained during an energy audit in the heating plant Vreoci in the Electric Power System of Serbia, are presented in the paper. Two steam boilers, rated at 120MW each, are installed in this heating plant, using coal as a fuel. The energy audit encompassed the measurements of the complete set of parameters needed to determine the thermal efficacy of boilers and the entire heating plant. Based on the measurement results, several technical measures for improving energy efficiency of the plant are proposed. The measures evaluated in the paper should contribute to the reduction of fossil fuel usage and CO2 emissions, thereby resulting in a significant impact in both financial and ecological areas